Application of special exercises to develop the fixation time and the skills of forehand and backhand groundstrokes in tennis players - Jihad Al-Rubaye , Saif Abbas; Hussein , Murtadha Sulttan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The present study was conducted on the Misan tennis clubs advanced players, in the premises of the tennis court of the Technical Institute in Misan. The study was conducted within the timeframe of August 2020 to December 2020. In the current study, the research community was represented by the players of the Misan Governorate team. A total of 8 players were selected as the participants for the study. All the participants were randomly allocated into two groups with n=4 in each group. The researcher formulated a set of exercises. These exercises were performed by the participants of the experimental group during their preparation phase and in the main training phase. The control group participants received training by exercises developed by the training coaches. The total number of training exercises was 8. In each training dose 4 exercises were included. In the present study the researchers concluded that there was a positive effect of the special exercises in developing the fixation time during the performance of the forehand and backhand groundstrokes.